Psychological Aspects of the Choice Theory Reality Therapy (CTRT) Approach on Sexual Misconduct: Cases In Women's Shelters - Izzah Supeni; Ahmad Jazimin Jusoh (International Journal of Education, Information Technology, and Others, 2021)
The purpose of this study was to examine the psychological component of the Choice Theory Reality Therapy (CTRT) approach to sexual misconduct at the Women's Protection Center. The case study approach was employed in this investigation, with seven study participants and four extra informants recruited using a purposive sample methodology. The data were gathered through interviews, document analysis, and observation. The study took place in women's shelters. The data were analyzed using textual analysis tools. The study's findings show that the psychological element of adolescents that is most required is love, whereas power is less needed. The consequences of this study were to serve as a reference and guide for counselors and researchers interested in assisting persons using the CTRT.